2012
DOI: 10.1002/jmri.23692
|View full text |Cite
|
Sign up to set email alerts
|

Fat‐referenced MR thermometry in the breast and prostate using IDEAL

Abstract: Purpose: To demonstrate a three-echo fat-referenced MR thermometry technique that estimates and corrects for time-varying phase disturbances in heterogeneous tissues. Materials and Methods:Fat protons do not exhibit a temperature-dependent frequency shift. Fat-referenced thermometry methods exploit this insensitivity and use the signal from fat to measure and correct for magnetic field disturbances. In this study, we present a fat-referenced method that uses interpolation of the fat signal to correct for phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 40 publications
0
50
1
Order By: Relevance
“…For data presented here, a phase-based fatreferenced technique was used to correct for the static B 0 drift [30]. Fat-referenced PRFS maps [25,[31][32][33] are computed as in Equation 2:…”
Section: Heating Experiments and Thermometrymentioning
confidence: 99%
“…For data presented here, a phase-based fatreferenced technique was used to correct for the static B 0 drift [30]. Fat-referenced PRFS maps [25,[31][32][33] are computed as in Equation 2:…”
Section: Heating Experiments and Thermometrymentioning
confidence: 99%
“…Because of this, the nuclear field experienced by hydrogen nuclei in water and fat may be different. Notably, Hofstetter et al measured a larger difference between the fat‐referenced temperature change and temperature probe readings in pork tissue and mayonnaise. These findings suggest that the spatial distribution of water and fat and the degree of homogeneity in that distribution play a role here.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have noted that fat‐referenced MR thermometry might have a larger error in tissues with a heterogeneous fat/water distribution, as there is a different magnetic susceptibility distribution between water and fat. However, other studies have shown that this technique works well in tissues with homogeneous fat/water distributions . In the present study, the fat/water phantom was constructed with a uniform mixture of water and peanut oil, and BAT is a fatty tissue with lipid and water protons that reside in the same cell compartment.…”
Section: Discussionmentioning
confidence: 98%